2021
DOI: 10.3389/fgene.2021.723360
|View full text |Cite
|
Sign up to set email alerts
|

Species and Phenotypic Distribution Models Reveal Population Differentiation in Ethiopian Indigenous Chickens

Abstract: Smallholder poultry production dominated by indigenous chickens is an important source of livelihoods for most rural households in Ethiopia. The long history of domestication and the presence of diverse agroecologies in Ethiopia create unique opportunities to study the effect of environmental selective pressures. Species distribution models (SDMs) and Phenotypic distribution models (PDMs) can be applied to investigate the relationship between environmental variation and phenotypic differentiation in wild anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…One of the limitations of our study is that we only used chicken populations that were available to us. Although the sampling was performed to represent major Ethiopian AEZs, no specific environmental-gradation approach was applied to inform the sampling, as has been done in a recent paper by Kebede et al (2021). Consequently, though fully valid, our study may not have surveyed all possible agro-climatic clines and the ecotypes presented here may not be an exhaustive list from Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the limitations of our study is that we only used chicken populations that were available to us. Although the sampling was performed to represent major Ethiopian AEZs, no specific environmental-gradation approach was applied to inform the sampling, as has been done in a recent paper by Kebede et al (2021). Consequently, though fully valid, our study may not have surveyed all possible agro-climatic clines and the ecotypes presented here may not be an exhaustive list from Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the method has been a powerful tool in the conservation efforts of wild species (Thorn et al, 2009) and has found applications for other diverse purposes such as assessing the risk from invasive species (Jiménez-Valverde et al, 2011), epidemiological studies (Cardoso-Leite et al, 2014), and estimating the effect of climate change on future distribution of a species (Jeschke and Strayer, 2008). In livestock, however, the use of ENM is still in its infancy with only a few available examples (Pitt et al, 2016;Lozano-Jaramillo et al, 2018;Vajana et al, 2018;Gheyas et al, 2021;Kebede et al, 2021). Pitt et al (2016) used MaxEnt for inferring the actual and historical distributions of early domestic fowl by modelling the environmental conditions of extant Red Jungle Fowl (RJF) with important conservation implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In livestock, the application of the ENM approach is still in its infancy, with only a few studies so far, primarily in chicken (Vajana et al, 2018;Lozano-Jaramillo et al, 2019;Gheyas et al, 2021;Kebede et al, 2021;Vallejo-Trujillo et al, 2022). Applying ENM on Ethiopian indigenous chickens, Gheyas et al (2021) identified six major environmental variables.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the author chose the extreme environments to identify signatures of positive selection in the genome of these populations associated with the selected environmental parameters. Kebede et al (2021) studied Ethiopian environmental gradients and using ENM classified the indigenous Ethiopian chicken's habitats into three agro-ecologies. They reported significant morphological differences between the chicken populations among these agro-ecologies, supporting them as chicken ecotypes (Kebede et al, 2021).…”
Section: Introductionmentioning
confidence: 99%